Searching The Shortest Route Of Delivery Using The A* Algorithm Case Study Jne Office In Jakarta Selatan - Faqih, Abdurrahman; Mutmainnah, Khonsa; Alief R, Muhammad Bakhara (Universitas Gajah Putih, 2021)
. Couriers deliver goods to many places every day. Therefore, the couriers need to find the shortest path between their intended locations. This is to save time, energy, and costs. The A* algorithm is one of the methods commonly used in finding the shortest path. By using this method, it is hoped that couriers will find it easier to find the shortest path when sending goods